La variabile religiosa nei Peace Studies (Stato, Chiese e pluralismo confessionale, 2025)
The religious shift in Peace StudiesThe article explores the evolving role of religion within Peace Studies, highlighting its shift from a marginal and ‘integrated presence’ to an autonomous and strategic variable in the analysis, management and transformation of conflicts. Adopting the paradigm of ‘constructive conflict’, it explores the ambivalent role of religion, which may serve either to intensify dynamics of radicalization and polarization or to foster reconciliation and social cohesion. Through a multidisciplinary approach, this study investigates the role of religious rhetoric as an internal communicative device within organizations, functioning both as a catalyst for conflicts and as a means of managing different challenges; furthermore, the paper reflects on the tools of ‘religious diplomacy’, emphasizing how interreligious dialogue and religious literacy can reinforce peacebuilding efforts. In this perspective, the religious variable emerges as a key factor for interpreting and transforming conflict dynamics, ultimately contributing to the establishment of an inclusive and lasting peace.SOMMARIO: 1. Introduzione - 2. La variabile religiosa nei Peace Studies: da ‘integrated presence’ a ‘objectified variable’ - 3. La variabile religiosa proiettata nei processi di costruzione di pace - 4. Conflitto e retoriche religiose nei recenti studi sulla pace - 5. Sulla correlazione tra retoriche religiose e conflittualità - 6. Fattore religioso e conflitti nel panorama contemporaneo - 7. La variable religiosa nei Peace Studies: strumenti di ‘religious diplomacy’ - 8. ‘Peacebuilding’: il ruolo dell’analfabetismo religioso e del dialogo interreligioso - 9. Conclusioni.